A estética dos becos em Cora Coralina ou “Um modo diferente de contar velhas estórias” - Clovis Carvalho Britto (Estudos de Literatura Brasileira Contemporânea)
This article examines the interconnections between literature, memory and the city in the work of Cora Coralina (1889-1985). From a topographic memory, Coralina elected the alleys as a privileged space for her work’s aesthetics. In this interpretive key, she observed social relations within Brazil in the nineteenth and twentieth centuries from a point of view that rehabilitates the margins. In several poems and tales, the city life is translated from life in the alleys, the characters who reside there, and relationships and reactions that it causes. We intend, therefore, to analyze the strategies used by the author to portray and criticize the reality of their time considering the alleys as metaphor and metonymy of your city. From a marginal insertion, especially due to prejudices regarding their age and condition of women, Cora developed an aesthetic of alleys where women and other minorities, not always numeric, become the center.